Intraduodenal nutrient infusion differentially alters intestinal nutrient sensing, appetite, and satiety responses in lean and obese subjects - Sundaresan, Sinju; Johnson, Connor; Dixon, Kala B.; Dole, Michael; Kilkelly, Donna; Antoun, Joseph; Flynn, Charles Robb; Abumrad, Naji N.; Tamboli, Robyn (The American journal of clinical nutrition, 2023)
Intestinal nutrient sensing regulates food intake and energy metabolism by acting locally and relaying nutritional status to the brain. It is unclear whether these mechanisms are altered in obese humans. We aimed to investigate differences in duodenal nutrient sensing in humans with or without obesity and the effects of transiently blocking vagal transmission on nutrient sensing, hunger, and appetite. In a single-blinded, randomized, cross-over design, subjects with or without obesity (n = 14 and n = 11, respectively) were infused intraduodenally with saline or a combination of glucose and oleic acid for 90 min (glucose load: 22.5 g, 1 kcal/min; oleic acid load: 10 g, 1 kcal/min) in the presence or absence of local anesthetic (benzocaine). Blood was sampled at 10-min intervals (120–240 min) and 15-min intervals until termination of the study for measurements of gut hormones, insulin, leptin, and C-peptide. Hunger and satiety sensations were scored using the visual analog scale, and hepatic glucose production and glucose oxidation rates were measured. Duodenal nutrient infusion in lean subjects led to a 65% drop in acyl ghrelin release and robustly increased cholecystokinin 8 (CCK-8) release (65%; P = 0.023); benzocaine infusion delayed this response (2-factor repeated-measures analysis of variance, P = 0.0065). In contrast, subjects with obesity had significantly blunted response to nutrient infusion, and no further effects were observed with benzocaine. Additionally, significant delays were observed in peptide YY (3-36), pancreatic polypeptide, glucose inhibitory peptide, and glucagon-like peptide 1 (7-36) response. No significant interactions were found between body mass index (BMI) or baseline hormone levels and areas under the curve for hormones except CCK-8 (BMI, P = 0.018; baseline CCK, P = 0.013). Nutrient-induced hunger and satiety sensations were impeded by benzocaine only in the lean cohort. Hunger and satiety sensations in subjects with obesity were not responsive to nutrient entry into the duodenum, and no additional effects were observed by blocking neural signaling. Nutrient-induced gut hormone release and response to transient vagal blockade are significantly blunted in subjects with obesity. This trial was registered at clinicaltrials.org as NCT02537314.